The Analysis of Third-Party Funds, State Sukuk, and Corporate Sukuk Towards Financial Deepening in Indonesia - Mery Mary; Elis Mediawati; Fitranty Adirestuty (Review of Islamic Economics and Finance (RIEF), 2019)
Sharia-based financial institutions are being developed in Indonesia, especially in Islamic banking and Islamic capital market institutions. The role of financial institutions in economic growth in Indonesia is defined as financial deepening. This study examines the variables of third party-funds, state Sukuk, and corporate Sukuk towards financial deepening. The used research method in this research was the causality method with a quantitative approach. The population in this study is Islamic banking and Islamic capital markets, which are registered at the Financial Services Authority (FSA). The sampling technique was saturation sampling. The used method in this research was the descriptive-explanatory method with multiple linear regression analysis. The dependent variable in this study is financial deepening. While, the independent variable in this study is the third-party funds, corporate Sukuk, and state Sukuk. The results show that third-party funds affect financial deepening, state Sukuk affects financial deepening, and corporate Sukuk does not affect financial deepening.